2021
DOI: 10.3390/healthcare9101324
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Just Culture and Empowerment on Patient Safety Activities of Hospital Nurses

Abstract: This study investigated the relationship among hospital nurses’ perceptions of a just culture, empowerment, and patient safety activities. It also determined the factors affecting the patient safety activities of nurses. This cross-sectional study included 189 nurses from four hospitals in South Korea. The survey was conducted from October to December 2019 using self-report questionnaires including items on socio-demographic characteristics, just culture, empowerment, and patient safety activities. Data were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 21 publications
5
17
1
4
Order By: Relevance
“…This research also found that just culture indirectly influences patient safety event reporting via safety climate. This finding is supported by the results of previous studies, which found that organizational factors, such as incident-reporting cultures, just cultures, and safety climates, have a significant effect on safety event reporting [7,15,45]. Our study also found that just culture has a direct effect on safety climate.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This research also found that just culture indirectly influences patient safety event reporting via safety climate. This finding is supported by the results of previous studies, which found that organizational factors, such as incident-reporting cultures, just cultures, and safety climates, have a significant effect on safety event reporting [7,15,45]. Our study also found that just culture has a direct effect on safety climate.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, in order to improve patient safety reporting by military hospital nurses, efforts to improve the overall system, create a safety culture, and to form a positive working environment should be conducted. Contrary to our expectations, as well as in contradiction to previous studies, just culture did not directly affect patient safety event reporting [7,15]. This study found that military nurses did not positively perceive the organization's just culture, which is consistent with previous studies on clinical nurses [15,48].…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations